ANALYSYS OF DIGITAL ECONOMY DEVELOPMENT IN UZBEKISTAN REPUBLIC - Tashmatov Salohiddin Zayniddinovich (International Journal of Economic Integration and Regional Competitiveness, 2024)
In the article we analysis a development of digital economy in Uzbekistan. Trends and perspectives of economy in information and communication sphere of Uzbekistan. The criteria of trust, transparency and accountability specific to corporate governance are gaining importance in improving the investment environment, ensuring financial stability and sustainable economic growth